Evaluation of Diagnostic Accuracy of Nuclear Medicine Imaging in Detecting Thyroid Disorders at Birat Medical College Teaching Hospital - Chaudhary , Amardeep; Kumar, Yadav Birendra; Prakash, Yadav Om; Yadav , Ajay Kumar (Nepalese Journal of Cancer, 2026)
Objective: To evaluate the diagnostic accuracy of nuclear medicine imaging in detecting thyroid disorders at a tertiary care center.Methods: This observational study included 120 patients suspected of thyroid dysfunction who underwent nuclear medicine imaging from January 2025 to December 2025. Thyroid scans were performed using Technetium-99m pertechnetate. Imaging findings were correlated with clinical assessment and laboratory investigations including T3, T4, and TSH levels.Results: Among the 120 patients, 72 (60%) were diagnosed with hyperthyroidism, 36 (30%) with hypothyroidism, and 12 (10%) were euthyroid with nodular lesions. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of nuclear imaging were 95%, 92%, 93%, and 94%, respectively.Conclusion: Nuclear medicine imaging is a highly sensitive and specific modality for diagnosing thyroid disorders and plays a crucial role in clinical decision-making.